Petrology, geochemistry and evolution of the Labrador Trough Basaltic Suite, Labrador and New Quebec. - Findlay, Jonathan. (University of Ottawa (Canada), 1996)
The central Labrador Trough is an Early Proterozoic volcano-sedimentary succession which preserves the remnants of a major magmatic province, the Labrador Trough Basaltic Suite (LTBS). The Menihek gabbros, which are distinctive members of the LTBS, form a sill-sediment complex with turbidites of the Menihek Formation. The Menihek gabbros often exhibit spectacular plagioclase glomeroporphyritic textures. Tholeiitic basalts of the LTBS (Le Fer and upper Menihek/Willbob basalts) exhibit many textural and geochemical similarities, despite a difference of $\sim$260 Ma in the ages of the two principal suites. The alkaline rocks of the LTBS (Nimish, lower Menihek and lower Murdoch basalts) exhibit strong compositional diversity, and it is probable that variations in mantle source composition and/or melting depths, crustal assimilation, fractional crystallization and post-crystallization processes influenced the geochemistries of these suites. The Nimish and lower Menihek basalts exhibit extended trace element patterns which indicate that their parental melts were derived primarily from a relatively undepleted mantle reservoir, but with variable contributions from a depleted source. The stratigraphic and geochemical characteristics of the LTBS suggest that magmatism accompanied crustal extension and formation of pull-apart basins on the thinned margin of the Superior craton. Initial cycle 1 sedimentation ($>$2169 Ma) was fluviatile and accompanied by localized alkaline volcanism, but subsequent subsidience and marine transgression led to deposition of shallow to deep water sediments, culminating with the Le Fer turbidites. Magmatic activity and sedimentation continued until at least 2142 Ma, at which point crustal extension and basin subsidence ceased, sedimentation was interrupted, and in places pre-existing strata were eroded. Crustal attenuation and basin subsidence again led to a transgressive marine sequence, culminating with the Menihek turbidites. Alkaline volcanism of the Nimish and lower Menihek formations accompanied early cycle 2 sedimentation, while turbidite deposition was accompanied by tholeiitic volcanism in the axial regions of the basin (Doublet terrane) and by emplacement of numerous gabbro sills in flanking regions (Howse zone). The Superior craton is likely to have formed the basement to the Labrador Trough succession throughout most of its evolution, but the eruption of late high-Mg basalts in the Doublet terrane, coupled with the emplacement of high-Mg magmas as sills, may record the late rupture of the continental crust. The continental crust thus acted as a density barrier to primitive partial melts until late in the evolutionary history of the Labrador Trough. The transition from alkaline to tholeiitic magmatism in each volcano-sedimentary cycle is thought to reflect progressive increases in the degree of decompressive partial melting in the upwelling, heterogeneous asthenospheric mantle during crustal attenuation. (Abstract shortened by UMI.)
Keywords: Geology.